ANALISIS KETERAMPILAN MEMBUKA DAN MENUTUP PELAJARAN DALAM PELAKSANAAN PEMBELAJARAN MATEMATIKA SD NEGERI 192 PEKANBARU - Oktaviani Oktaviani; Syahrilfuddin Syahrilfuddin; Lazim. N Lazim. N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The background of this research is the importance of applying the skills to open and close lessons in the process of implementing classroom learning. This study aims to describe the teacher's skills in opening and closing learning in the implementation of mathematics learning at SD Negeri 192 Pekanbaru. The type of research used is descriptive qualitative. The subject of the research was the IV grade teacher named Wiki Destalia, S.Pd.I. Data collection techniques use observation, interviews, and documentation. Test the credibility of the data through triangulation and data analysis techniques, namely data management, data reduction, data presentation, and conclusion drawing. The results achieved in this study is that the teacher has implemented the skills of opening and closing lessons in the process of implementing mathematics learning, but there are several indicators on the components opening and closing lessons that are rarely even seen by teachers, such as indicators of student interaction with students very rarely seen, giving rise to motivation that the indicator presents contradictory ideas to provoke students 'interest in learning material and pay attention to students' interests.